Indonesian Football 1951-1967: The Golden Age? - Budi Harjo Sayoga; Didik Pradjoko; Agus Setiawan (Interdisciplinary Social Studies, 2025)
The background of this study departs from the phenomenon that, although Indonesia has not made significant global achievements, the period is considered the peak of the national team's accomplishments at the Asian and world levels. This study discusses the journey of Indonesian football during the period 1951–1967, a period often referred to as the "golden age." The purpose of this research is to trace the extent to which the achievements of the Indonesian national team deserve to be called the golden age and to analyze the socio-political influences on the development of national football during the reign of President Sukarno. The research method used is descriptive-historical, employing literature studies, national archives, contemporary newspapers, and interviews with historical actors. The results of the study show that the 1950s–1960s era was a golden period of Indonesian football, marked by successes such as qualifying for the 1956 Melbourne Olympics, achieving fourth place at the 1954 Manila Asian Games, winning bronze at the 1958 Tokyo Asian Games, as well as becoming champions of non-FIFA international tournaments like the Merdeka Games and the Aga Khan Gold Cup. The main supporting factor was Sukarno's political backing, which positioned sports as a means of diplomacy and nation-building. However, this period was also marred by setbacks, including the 1962 bribery scandal and international political sanctions after Ganefo. Thus, the period 1951–1967 can be categorized as the golden age of Indonesian football from the perspective of historical achievements and national identity.